Nexus of Finacial Inclusion and Human Development as an Important Role in Economic Growth: Evidence from ASEAN Countries - Zainuri; Agus Mahardiyanto; M. Saleh; M. Fahorrazi; Tyas Arthasari; Naziaa Adeel (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Financial inclusion is one of the financial indicators that play a role in providing access to financial products to the public, the high level of equitable access to finance in the community can be an essential milestone in reviving the economic cycle and being a threat to the financial system. Implementing a country's financial inclusion will be successful if it is balanced with an adequate quality of society because special knowledge is needed in choosing access to financial services. The financial inclusion and human development nexus is expected to assist the government in implementing sustainable economic development. This study aims to analyze the relationship between the financial inclusion index and HDI, the financial inclusion index and HDI nexus with GDP, and the financial stability problem in developing ASEAN countries is still motivated by the high level of banking NPLs. This study uses panel data with the Generalized Method of Moment as an analytical method. The selection of the vulnerable research year is motivated by the phenomenon of the financial crisis, Brexit to Covid-19.